THE INFLUENCE OF CSR DIMENSION ON INVESTOR ATTENTION DURING THE COVID-19 - Harmayuni, Vella; Luthan, Elvira; Fontanella, Amy (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
Investor attention reacts to the company’s newly released information, especially positive information or positive signal. Since COVID-19 pandemic, CSR is one of the positive signals from company. This study aims to examine the effect of each CSR dimension on investor attention during the COVID-19 pandemic and prove which form of CSR category attract investor attention the most in times of crisis. The research uses quantitative methods, secondary data forms, and linear regression techniques. The results of the study show that each CSR dimension has a significant correlation on investor attention and the people dimension or social performance is the form of CSR that attracts investor attention the most during the COVID-19 pandemic. So, it concluded that companies need to consider CSR activities during times of crisis.